Normal Values of Esophageal Distensibility and Distension-Induced Contractility Measured by Functional Luminal Imaging Probe Panometry - Carlson, Dustin A.; Kou, Wenjun; Lin, Zhiyue; Hinchcliff, Monique; Thakrar, Anjali; Falmagne, Sophia; Prescott, Jacqueline; Dorian, Emily; Kahrilas, Peter J.; Pandolfino, John E. (Clinical gastroenterology and hepatology, 2019)
Functional luminal imaging probe (FLIP) panometry provides a comprehensive evaluation of esophageal functional at the time of endoscopy, including assessment of esophageal distensibility and distension-induced esophageal contractility. However, the few and inconsistent findings from healthy individuals pose challenges to the application of FLIP to research and clinical practice. We performed FLIP panometry in asymptomatic volunteers. We performed a prospective study of 20 asymptomatic volunteers (ages, 23–44; 14 women) who were evaluated with 16-cm FLIP positioned across the esophagogastric junction (EGJ) and distal esophagus (and in 8 subjects also repositioned at the proximal esophagus) during sedated upper endoscopy. FLIP data were analyzed with a customized program that generated FLIP panometry plots and calculated the EGJ-distensibility index (DI) and distensibility plateaus (DP) of distal and proximal esophageal body. Distension-induced esophageal contractility was also assessed. The median EGJ-DI was 5.8 mm2/mm Hg (interquartile range [IQR], 4.9–6.7 mm2/mm Hg); all 20 subjects had an EGJ-DI greater than 2.8 mm2/mm Hg. The median DP values from all subjects tested were 20.2 mm (IQR, 19.8–20.8 mm) at the distal body, 21.1 mm (IQR, 20.3–22.9 mm) at the proximal body, and greater than 18 mm at both locations. Repetitive antegrade contractions (RACs) were observed in all 20 subjects; in 19 of 20 (95%) subjects, the RAC pattern persisted for 10 or more consecutive antegrade contractions. Normal parameters of FLIP panometry are EGJ-DI greater than 2.8 mm2/mm Hg, DP greater than 18 mm, and antegrade contractions that occur in a repetitive pattern (RACs)—these can be used as normal findings for esophageal distensibility and distension-induced contractility. These values can be used in comparative studies of esophageal diseases, such as achalasia and eosinophilic esophagitis, and will facilitate application of FLIP panometry to clinical practice.